Combining Geographica Information Systemas (GIS) and mathematical modeling to location-allocation problems in education facilities management - Mapa, Silvia Maria Santana (2007)
The objective of this research was to evaluate the quality of the solutions for the facility location-allocation problem generated by the TransCAD GIS software, obtained after the combined use of its Facility Location and Transportation Problem routines, when compared with the optimal solutions obtained from an optimisation model based on Mixed Integer Linear Programming (MILP). For this purpose the models were applied to locate day-care centers and allocate the demand (0-3 year old children) in the city of São Carlos, State of São Paulo, Brazil. Different scenarios were developed to simulate the opening/closing of units and compare with the current situation. Results showed that when the capacity of the facilities is considered, the MILP model gives results 37% better than the TransCAD models, and additionally identifies different locations for the new facilities.